Non-typeable Haemophilus influenzae protein vaccine in adults with COPD: A phase 2 clinical trial. Issue 41 (24th September 2019) - Wilkinson, Tom M.A.; Schembri, Stuart; Brightling, Christopher; Bakerly, Nawar D.; Lewis, Keir; MacNee, William; Rombo, Lars; Hedner, Jan; Allen, Martin; Walker, Paul P.; De Ryck, Iris; Tasciotti, Annaelisa; et al.
Highlights: An investigational NTHi vaccine was tested for the first time in adults with COPD. The vaccine had acceptable safety and reactogenicity. Vaccine-elicited antibody concentrations were higher than baseline 1 year post-dose 2. Abstract: Loss of airway microbial diversity is associated with non-typeable Haemophilus influenzae (NTHi) infection and increased risk of exacerbation in chronic obstructive pulmonary disease (COPD). We assessed the safety and immunogenicity of an investigational vaccine containing NTHi antigens, recombinant protein D (PD) and combined protein E and Pilin A (PE-PilA), and AS01 adjuvant in adults with moderate/severe COPD and prior exacerbations. In this phase 2, observer-blind, controlled trial (NCT02075541), 145 COPD patients aged 40–80 years randomly (1:1) received two doses of NTHi vaccine or placebo 60 days apart, on top of standard care. Reactogenicity in the 7-day post-vaccination period was higher following NTHi vaccine than placebo. Most solicited adverse events (AEs) were mild/moderate. At least one unsolicited AE was reported during the 30-day post-vaccination period by 54.8% of NTHi vaccine and 51.4% of placebo recipients. One serious AE (placebo group) was assessed by the investigator as vaccine-related. Anti-PD, anti-PE and anti-PilA geometric mean antibody concentrations increased up to 30 days after each NTHi vaccine dose, waned thereafter, but remained higher than baseline (non-overlapping confidence intervals) up to 13 months post-dose 2. The frequency of specific CD4 + T cells increased following two doses of NTHi vaccine and remained higher than baseline. Exploratory analysis showed a statistically non-significant lower yearly rate of moderate/severe exacerbations in the NTHi vaccine group than following placebo (1.49 versus 1.73) in the one-year period post-dose 2, with estimated vaccine efficacy of 13.3% (95% confidence interval −24.2 to 39.5; p = 0.44). The NTHi vaccine had an acceptable safety and reactogenicity profile and good immunogenicity in adults with COPD.